In vitro antioxidant and in vivo xanthine oxidase inhibitory activities of Pandanus amaryllifolius in potassium oxonate-induced hyperuricemic rats - Shukor, Nur Afira Ahmad; Ablat, Abdulwali; Muhamad, Nur Airina; Mohamad, Jamaludin (Wiley, 2018)
Xanthine oxidase (XO) plays an important role in the regulation of uric acid and prevents it from being overproduced as in hyperuricemia disease. The combined effects of antioxidant and xanthine oxidase inhibitor would become a promising approach for hyperuricemia treatment. In this research, the antioxidant and xanthine oxidase inhibitory activities of Pandanus amaryllifolius leaf were evaluated. The leaf water extract (PA-W) showed highest total phenols, and petroleum ether extract (PA-PE) showed highest total flavonoids contents. The antioxidant activity of DPPH, metal chelating and hydrogen peroxide was highest in PA-W extract. The treatment of PA-W extract at 1000 mg kg−1 body weight in potassium oxonate-induced hyperuricemic rats showed significant (P < 0.001) decrease in serum uric acid level by 85% and XO activity by 64%, respectively, as compared to the hyperuricemic rats. In conclusion, the P. amaryllifolius possess the dual effect of antioxidant and XO inhibition as potential therapeutic agents in the hyperuricemia treatment.